Implementation of Digital Textbooks in Islamic Religious Education to Develop Critical Thinking Skills of University Students - Subakti, Hani; Nasir, Muhammad; Salehudin, Mohammad (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The development of globalization and digital technology has brought significant changes to higher education, driving the adoption of technology-based learning to create a more interactive and relevant experience for the current generation of students. This study aims to analyze the implementation of digital textbooks in Islamic Religious Education (IRE) at public universities, focusing on the development of students' critical thinking skills. Using a qualitative approach with a case study design, this research was conducted at a university in East Kalimantan, involving 15 informants from lecturers, students, and program administrators. Data were collected through non-participant observation, semi-structured interviews, and documentation, then analyzed using an interactive model. The findings indicate that the implementation of digital textbooks in IRE is carried out in three stages: planning, implementation, and evaluation. The digital textbooks have been proven to enhance students' ability to analyze religious issues, formulate logical arguments, and foster empathy and tolerance toward religious differences. This research also enriches the educational literature by affirming that digital textbooks not only effectively strengthen higher-order thinking skills (HOTS), but also function as a pedagogical tool that supports inclusive and multicultural religious education. Therefore, digital textbooks can be a transformative tool in shaping critical, reflective, and inclusive students in higher education.